Phytochemical Study of Ethanol Extract of Sengkubak Leaves (Pycnarrhena cauliflora (Miers) Diels) and Molecular Docking Analysis as a Potential Anti-Breast Cancer Agents - Yuneta; Nugroho, Wahyu; Kalalinggi, Septaria Yolan; Toepak, Erwin Prasetya (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Reactive Oxygen Species (ROS) are a group of free radicals that play a major role in causing oxidative stress, which can trigger the development of degenerative diseases such as cancer. Sengkubak (Pycnarrhena cauliflora (Miers) Diels) contains antioxidant that may help protect the body from free radical exposure. This study aims to identify the metabolite compounds present in Sengkubak leaves through GC-MS analysis and to evaluate their anticancer potential of its major metabolites through in silico molecular docking analysis. The leaf simplicia was extracted using the maceration method with ethanol as the solvent. The analyses performed included GC-MS analysis and molecular docking analysis of the major compounds identified by GC-MS to evaluate their anticancer potential. GC-MS analysis identified a total of 84 compounds, with the five major ones being Phytol, Farnesol isomer a, L-Gala-L-ido-octose, E-11-HexadecenoicAacid ethyl ester, and Pentadecanoic acid ethyl ester. Furthermore, molecular docking analysis of the five major compounds demonstrated potential anticancer activity against breast cancer targets.